Pengaruh Tingkat Literasi Finansial dan Persepsi Risiko terhadap Perilaku Konsumtif Impulsif pada Mahasiswa Ekonomi Institut Syekh Abdul Halim Hasan Binjai - Bangun, Putri Ramadhani; Syahputri, Alfiani Rizky; Mulkhan, Balya Ibnu; Yanti, Ita Novi; Prislin, Lidya Clara; Maisyarah Maisyarah; Athar, Gadis Arniyati (Kajian Ekonomi dan Akuntansi Terapan, 2025)
This study aims to analyze the effect of financial literacy and risk perception on impulsive consumptive behavior on students of the Faculty of Economics, Sheikh Abdul Halim Institute impulsive consumptive behavior in students of the Faculty of Economics, Sheikh Abdul Halim Hasan Institute Binjai. Using a quantitative approach with an explanatory survey method, this study involved 56 respondents selected using accidental sampling technique. The regression analysis results show that financial literacy has a significant positive effect on consumptive behavior (B = 1.157; sig. = 0.000), while risk perception has a significant negative effect (B = -0.555; sig. = 0.017). Simultaneously, these two variables contribute significantly to consumptive behavior with a coefficient of determination (R²) of 61.4%. The results of this study reveal that high financial literacy can increase the tendency of consumptive behavior due to increased confidence in financial management, while high risk perception can suppress consumptive behavior through awareness of potential losses. This study emphasizes the importance of a holistic approach in the formation of healthy financial behavior, involving the improvement of financial literacy as well as education related to risk perception. The findings are expected to contribute to the development of more effective financial education strategies for economics students.